Fish Collagen Surgical Compress Repairing Characteristics on Wound Healing Process In Vivo - Jingjing Chen (Marine Drugs, 2019)
The development of biomaterials with the potential to accelerate wound healing is a great challenge in biomedicine. In this study, four types of samples including pepsin soluble collagen sponge (PCS), acid soluble collagen sponge (ACS), bovine collagen electrospun I (BCE I) and bovine collagen electrospun II (BCE II) were used as wound dressing materials. We showed that the PCS, ACS, BCE I and BCE II treated rats increased the percentage of wound contraction, reduced the inflammatory infiltration, and accelerated the epithelization and healing. PCS, ACS, BCE I, and BCE II significantly enhanced the total protein and hydroxyproline level in rats. ACS could induce more fibroblasts proliferation and differentiation than PCS, however, both PCS and ACS had a lower effect than BCE I and BCE II. PCS, ACS, BCE I, and BCE II could regulate deposition of collagen, which led to excellent alignment in the wound healing process. There were similar effects on inducing the level of cytokines including EGF, FGF, and vascular endothelial marker CD31 among these four groups. Accordingly, this study disclosed that collagens (PCS and ACS) from tilapia skin and bovine collagen electrospun (BCE I and BCE II) have significant bioactivity and could accelerate wound healing rapidly and effectively in rat model.